Teachers’ Conceptions of the Role of Master of Elementary Education in Enhancing Their Competences - Bachtiar; Widya Rizky Pratiwi (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
Blended learning has emerged as one of the most popular and cutting-edge learning strategies implemented in the Post Covid -19. However, little research has been conducted to investigate teachers’ conceptions of implementing blended learning in the Indonesian context and the impact of Master of Elementary Education (MEE) Universitas Terbuka (UT) Indonesia on teachers’ competencies. This research investigates the advantage of teachers’ involvement as students in MEE UT. This research also intends to discover student-teacher challenges in utilizing blended learning as an emerging learning method of Post Covid-19. This research employed a convergent parallel design of Mixed Method Research (MMR) by inviting 20 student-teachers to participate in the questionnaire and 4 student-teachers in the semi-structured interviews. The participants were from MEE UT. The study findings found that despite some challenges that the teachers faced in the early stages of Covid -19, the teachers also viewed Covid -19 as a blessing in disguise, where the participants learned a lot about how to conduct learning in a fully online mode. The research findings also noted that the participants’ involvement in MEE UT has the teachers enhance their competencies, including Technological Pedagogical Content Knowledge (TPCK). Another worth finding is that blended learning has been viewed as a teaching strategy that meets the demand of instructional fits post Covid -19. This study includes evidence, implications of the results, and suggested directions for future instruction-related research.